Komparativní analýza standardů finanční gramotnosti v České republice a vybraných zahraničních státech - Karel Ševčík; Tomáš Janko (Karolinum Press, 2018)
The purpose of financial literacy, to help students manage everyday financial situations, is generally appreciated. The conditions for implementation of the financial literacy into school curricula may however differ significantly in various states. In the presented study the planned curriculum for financial education is analyzed. The aim is to compare the standards for financial literacy in the Czech Republic and other selected countries in terms of basic financial dimensions and categories. Methodology of the study is patterned on the FLin€VET program which sought to compare conceptions of financial literacy among various European states. In total 4 standards from the Czech Republic, Australia, Japan and United Kingdom are analyzed and compared. The results suggest that in the Czech standards topics related to pupils' orientation in financial relations are emphasized. However, the issues which would promote pupils' use of financial knowledge in authentic life situations are underestimated, compared to the standards of other states.